The Wnt/β-Catenin Signaling Pathway as a Target in Drug Discovery - Fumi Takahashi-Yanaga; Toshiyuki Sasaguri (Elsevier, 2007)
The cell signaling cascades provoked by Wnt proteins (the Wnt signaling pathways), which are well conserved through evolution, play crucial roles to maintain homeostasis of a variety of tissues such as skin, blood, intestine, and brain, as well as to regulate proliferation, morphology, motility, and fate of cells during embryonic development. Among these pathways, the signal transduction through β-catenin (the Wnt/β-catenin signaling pathway) has been most intensively studied because this signal regulates the expression of a number of genes essential for cell proliferation and differentiation and also this pathway is perturbed in a number of diseases such as cancers, bone diseases, and cardiovascular diseases. However, there is no therapeutic agents that can selectively modulate the Wnt/β-catenin signaling pathway, although some existing drugs (e.g., non-steroidal anti-inflammatory drugs, vitamins, and imatinib mesylate) have been suggested to inhibit this pathway. Here we provide an overview of the Wnt/β-catenin signaling pathway: its roles in physiology and pathology and the possibility as a target in development of new drugs. Keywords:: Wnt/β-catenin signaling, cancer, calcification, drug development, differentiation-inducing factor